2015
DOI: 10.1016/j.neubiorev.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Stress habituation, body shape and cardiovascular mortality

Abstract: High cardiovascular mortality is well documented in lean phenotypes exhibiting visceral fat accumulation. In contrast, corpulent phenotypes with predominantly subcutaneous fat accumulation display a surprisingly low mortality. The term 'obesity paradox' reflects the difficulty in understanding the biological mechanisms underlying these clinical observations. The allostatic load model of chronic stress focuses on glucocorticoid dysregulation as part of a 'network of allostasis' involving autonomic, endocrine, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 174 publications
(222 reference statements)
4
94
0
8
Order By: Relevance
“…Officers also need support in the aftermath of harm to the physiological systems that respond to stressor exposure, such as increasing awareness of risks and specific practices in police work that may help reduce individual vulnerability to stressors. Helping officers acquire skills to habituate to the stressors of police work may possibly change how exposures affect their physiology over time and perhaps prevent increases in cardiovascular risk (Peters & McEwen, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Officers also need support in the aftermath of harm to the physiological systems that respond to stressor exposure, such as increasing awareness of risks and specific practices in police work that may help reduce individual vulnerability to stressors. Helping officers acquire skills to habituate to the stressors of police work may possibly change how exposures affect their physiology over time and perhaps prevent increases in cardiovascular risk (Peters & McEwen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Reactivity of the HPA axis to induced psychosocial stress has been prospectively associated with the incidence of hypertension (Hamer & Steptoe, ). Four types of physiological responses contribute to and reflect maladaptation to stressor exposures: (a) frequency and intensity of responses, (b) failure to habituate after a repeated stressor exposure, (c) failure to terminate adaptive autonomic and neuroendocrine responses, and (d) failure to respond adequately to a challenge (McEwen & Gianaros, ; Peters & McEwen, ). The cumulative wear and tear of the physical and social environments (allostatic load) dictate an individual's response to stressors and their manifestations (McEwen, ).…”
Section: Introductionmentioning
confidence: 99%
“…The approach used to compute ARI here for hazard of all-cause mortality could also be extended to derive risk indices customized for specific causes of death and morbidity outcomes such as heart disease, stroke, or diabetes, which could facilitate individualized cost-benefit consideration in deciding what medical interventions to undertake [6971]. One recent study found that anthropometric indices (ABSI and WC/ H ratio) were correlated with Framingham and SCORE 10-year cardiovascular risk estimates in a nationally representative Turkish sample [72], while another study found anthropometry-based indices (specifically ABSI) to predict cardiovascular disease in middle-aged and elderly Dutch adults as well as a risk model that included laboratory measurements [73], highlighting the potential for utilization of a combination of several readily obtained body measurements for cardiometabolic risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the better they adjust their beliefs about uncertainty, the better they are able to predict future outcomes, thus reducing stress resulting from uncertainty. However, when the uncertainty becomes chronic and cannot be reduced it leads continuous and ineffective physiological stress reactions that cause depression, cognitive impairment, infarction, and stroke in the long term (Peters & McEwen, 2015).…”
Section: Underlying Stress Processesmentioning
confidence: 99%